2018
DOI: 10.1186/s13046-018-0899-8
|View full text |Cite
|
Sign up to set email alerts
|

An ABCG2 non-substrate anticancer agent FL118 targets drug-resistant cancer stem-like cells and overcomes treatment resistance of human pancreatic cancer

Abstract: BackgroundPancreatic cancer is a deadly disease with a very low 5-year patient survival rate of 6–8%. The major challenges of eliminating pancreatic cancer are treatment resistance and stromal barriers to optimal drug access within the tumor. Therefore, effective molecular targeting drugs with high intra-tumor access and retention are urgently needed for managing this devastating disease in the clinic.MethodsThis study has used the following in vitro and in vivo techniques for the investigation of exceptional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 81 publications
7
50
0
Order By: Relevance
“…Consistently, FL118 appears to use multiple mechanisms to induce pancreatic cancer killing as well [80,98]. Furthermore, toxicity studies with FL118 at low, middle and high doses in beagle dogs indicated that at only the high dose, some of the 39 hematopoietic and biochemical parameters tested slightly changed without other FL118-related clinical observations including dog behavior, food consumption and body weights [80].…”
Section: Fl118mentioning
confidence: 92%
See 3 more Smart Citations
“…Consistently, FL118 appears to use multiple mechanisms to induce pancreatic cancer killing as well [80,98]. Furthermore, toxicity studies with FL118 at low, middle and high doses in beagle dogs indicated that at only the high dose, some of the 39 hematopoietic and biochemical parameters tested slightly changed without other FL118-related clinical observations including dog behavior, food consumption and body weights [80].…”
Section: Fl118mentioning
confidence: 92%
“…DNA microarray studies showed that FL118 does not inhibit the expression of cIAP1, Bcl-2, Bcl-XL, Bcl-2, Bcl2A1, Bcl-w, Bcl-B, Bcl2L12, Bcl2L13, Bcl-G and Bcl2L15 (unpublished data), indicating additional selectivity of FL118 in its molecular targets. Furthermore, FL118 also inhibits MdmX/Mdm4 [79], a critical oncogenic protein involved in p53 pathway, and ERCC6 [80], a critical regulator in DNA repair. Importantly, while FL118 downregulation of MdmX induced senescence in cancer cells with wild type p53, FL118 exhibits even higher efficacy to inhibit cell growth and induce apoptosis in cancer cells without functional p53 (mutated or null) [79].…”
Section: Fl118mentioning
confidence: 99%
See 2 more Smart Citations
“…5 In addition, FL118 was shown to selectively and independently inhibit additional anti-apoptotic genes including Mcl-1, XIAP and cIAP2. In preclinical settings, FL118 showed a favorable toxicity profile in experimental animals, 6 and an effective antitumor activity against human colon and head-and-neck tumors in a topoisomerase I-and P53 status-independent manner. 5,7 The latter is of importance for MM, since mutations or the loss of P53 encoding gene, as through the deletion of chromosome 17p, are characteristics of high-risk MM with poor prognosis.…”
mentioning
confidence: 99%